Influence of kitesurf equipment on injury rates - Baumbach, S. F.; Stawinski, T.; Schmitz, D.; Schoeneberg, C.; Jäger, M.; Wedemeyer, C.; Kauther, M. D. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: Various injuries in kitesurfing (KS) have been reported so far. The aim of this study was to validate the effect of different kite designs and safety equipment on the injury rate compared to older studies. METHODS: A retrospective epidemiological study based on an anonymous face-to-face survey was conducted amongst active kitesurfers. The questionnaire consisted of 66 questions focusing on the equipment used, injury rates, overuse injuries and gender differences. A stepwise Poisson-Model was used to identify injury-associated factors. RESULTS: A total of 202 kitesurfers with a mean age of 31.8±9.1 years and 698.2±931.5 hours of KS experience were included. 2613 injuries were recorded (18.5/1000 hours KS). Almost 50% were hematomas, bruises or cuts. 3.9% of all injuries (0.71/1000 hours KS) were time-loss injuries of more than one week. Female kitesurfers had a significantly greater injury rate, were less experienced and fewer of them used C-kites. Height, weight, primary kite spot, experience, physical activity, warm-up/stretching, the type of kite and control bar used, and the use of a board leash were independent factors associated to injury rate. The lower extremity, the elbow, thorax and abdomen were at risk for overuse injuries. CONCLUSIONS: An influence of equipment on injuries could be statistically shown. The overall injury rate in KS did not decline in the last decades, but time-loss injuries did.